KAJIAN BEBAN PENCEMARAN LIMBAH CAIR INDUSTRI KECIL MENENGAH (IKM) BATIK KLASTER TRUSMI KABUPATEN CIREBON - Adi Sulaksono; Hefni Effendi; Budi Kurniawan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Growing number of Indonesian Batik SMEs has been started since UNESCO announced batik as world heritage from Indonesia in 2009. However, this condition also brings negative impact related to water pollution. Huge variety of dyestuff always has been a challenge in estimating total pollution load from this sector. This study aim to estimate pollution load of some key parameters (BOD5, COD and TSS) of wastewater generated by Batik SMEs in Trusmi cluster. By calculating pollution load factor per unit product (PLU) trough analyzing waste water quality and quantity in every step of batik making process and considering type of fabric (cotton and silk) and type of dyestuff (Naphtol and Indigosol) as variable, it can be concluded that the PLU factor for BOD5 and TSS is associated to the type of fabric, meanwhile COD parameter is associated to the type of dyes. By multiplying the PLU factor with total production capacity from all SMEs in Trusmi cluster, it can be estimated that the total pollution load range in Trusmi area for BOD is at 5,9 – 39,5 ton/year; COD at 112-426 ton/year; and TSS at 4,88-16,3 ton/year.Keywords: batik, SMEs cluster, pollution load factor, waste water